(untitled) (Revista Sistemas de Producción Agroecológicos, 2025)
In order to publicize the research conducted at the Faculty of Agricultural Sciences and Natural Resources (FCARN) of the Universidad de los Llanos, the FCARN Researchers Meeting has been held since 2013. This academic event provides the academic community with a space to attend lectures and conferences that present the advances in the five lines of research of the Faculty: Animal, Agricultural and Environmental Health; Agricultural Production; Rural and Territorial Development; Agroindustrial Production Systems; and Hydrobiological Resources. In the 2024 version, the Research Groups attached to the Faculty participated not only in the presentation of oral and poster presentations, but also in the organization and logistical support of the event and the trade fair and university enterprises. Lines of Research: • Animal, Agricultural and Environmental Health. • Agricultural Production. • Rural and Territorial Development. • Agroindustrial Production Systems. • Hydrobiological Resources.